Transforming Closed-Loop Banking Ecosystem: A Qualitative Analysis of Corporate Relationship Bankers’ Perspectives in Indonesia - Mahadewi, Lufina (Universitas Brawijaya, Indonesia, 2025)
Banking challenges resulting from liquidity-tightening conditions for loan growth and funding require a banking transformation strategy to orchestrate the banking ecosystem. This study aims to uncover the strategies employed by banks to address current challenges through banking transformation towards a closed-loop banking ecosystem in the context of developing countries, specifically Indonesia, from the perspective of corporate relationship bankers. This qualitative research was conducted exploratively using the grounded theory method. Data collection was conducted through semi-structured interviews with 18 corporate relationship bankers in the corporate segment of state-owned and private banks. Thematic analysis was employed to identify the model strategy for a closed-loop banking ecosystem. This study reveals the strategy formation for a closed-loop banking ecosystem in banking transformation and development, addressing banking challenges in Indonesia. This study examines the role of corporate relationship bankers in transforming the closed-loop banking ecosystem, specifically as orchestrators of a closed-loop banking ecosystem model characterized by seamless business processes and effective risk management. Theoretically, this study reveals how the formation of a closed-loop banking ecosystem strategy model confirms and extends existing theoretical perspectives on resource-based theory for the development of banking capabilities in resource-constrained banking environments. This study emphasizes the development of resource-based theory that highlights capabilities multipliers, contextual capabilities, adaptive capabilities, and the real-time dynamism of the closed-loop banking ecosystem.